1970
DOI: 10.2151/jmsj1965.48.1_18
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Features of Thermal Convection in a Plane Couette Flow

Abstract: An investigation is made of some features of perturbation superimposed in a plane Couette flow with unstable stratification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
77
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 15 publications
7
77
0
Order By: Relevance
“…This synoptic-scale condition produced remarkably strong wind in the upper troposphere on 17 April. Asai (1970) investigated the features of convection in a current with vertical shear and showed the relationship among the vertical momentum transfer ðsÞ, the amplification rate of perturbation ðUWÞ, and the Richardson number ðRiÞ. When Ri is small (vertical wind shear is large), both s and UW are small, or convective activity is inhibited.…”
Section: Differences In Cloud Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…This synoptic-scale condition produced remarkably strong wind in the upper troposphere on 17 April. Asai (1970) investigated the features of convection in a current with vertical shear and showed the relationship among the vertical momentum transfer ðsÞ, the amplification rate of perturbation ðUWÞ, and the Richardson number ðRiÞ. When Ri is small (vertical wind shear is large), both s and UW are small, or convective activity is inhibited.…”
Section: Differences In Cloud Activitymentioning
confidence: 99%
“…Asai (1970) used a constant lapse rate of temperature and constant vertical shear; however, in the present study we use values averaged over 7000 to 11000 m ASL, where wind shear is large. Ri values at 0800, 1000, and 1200 UTC on 17 April are 0.022, 0.021, and 0.023, respectively.…”
Section: Differences In Cloud Activitymentioning
confidence: 99%
“…Yagi (1985) and Yagi et al (1986) analyzed GMS images and upper-air sounding data and indicated that the axes of the transversal cloud bands were parallel to the vertical wind shear vector of horizontal winds. In addition, by applying the linear theory of the thermal instability in the vertical shear flow (Asai 1970a(Asai , 1970b(Asai and 1972, Yagi (1985) proposed that the transversal cloud bands were produced from longitudinal-mode (shear-parallel mode) roll convections. Recently, Shimizu and Tsuboki (2005) analyzed the transversal cloud band near the coast of the Hokuriku district on the basis of dual-Doppler radar observations.…”
Section: Introductionmentioning
confidence: 99%
“…This result suggests that the formation process of ice/snow particles plays an important role in the formation of the three-dimensional kinematic structures of longitudinal-mode snowbands. Although linear theories succeeded in explaining the formation of cloud streets by horizontal roll vortices (e.g., Asai 1970;Brown 1970;Kuettner 1971), they cannot explain the three-dimensional kinematic structures of longitudinal-mode snowbands. Kobayashi et al (1992) observed the merging phenomena of longitudinal-mode snowbands.…”
Section: Introductionmentioning
confidence: 99%